Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan pada PT. Indonesia Prima Poperty Tbk Jakarta Pusat - Ramang, Grace D. P.; Tumbel, Tinneke M.; Rogahang, Joula J. (JURNAL ADMINISTRASI BISNIS, 2019)
This study aims to determine the financial performance of PT. Indonesia Prima Property, Tbk Jakarta Pusat by using financial ratio analysis from 2016 to 2018. Financial ratios analyzed include Current Ratio (CR), Quick ratio (QR), Total Assets Turnover (TAT), Net Profit Margin (NPM) , Gross Profit Margin (GPM), and Debt to Assets Total (DtAT). The data used in this study are in the form of financial statement data for 2016 - 2018. From the analysis of the data it can be seen that the liquidity ratio of PT. Indonesia Prima Property Tbk seen from CR in 2016 - 2018, in three years it was 2.78%, 4.28%, and 0.80% while the QR in 2016 - 2018 was 2.38%, 3.83%, 0.72%. The activity ratio of PT Indonesia Prima Property Tbk seen from TAT in three years is 0.56%, 0.43%, 0.03% has decreased every year this happens because the number of goods to be sold has not been much from the sale. PT Indonesia Prima Property Tbk’s profitability ratio seen from NPM in three years is 0.02%, 0.04%, 0.06% while GPM in three years is 0.49%, 0.44%, 0.37%. The Solvency Ratio of PT Indonesia Prima Property Tbk seen from DtAT in three years is 0.03%, 0.02%, 0.09% experiencing ups and downs because it is funded by capital in a solvable condition.